2010 Fifth IEEE International Symposium on Electronic Design, Test &Amp; Applications 2010
DOI: 10.1109/delta.2010.47
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable multivariable MEMS sensor array

Abstract: Research into operational aspects of mini unmanned aerial vehicles (UAV) and structural health monitoring systems (SHM) is being conducted at the Defence Science and Technology Organisation and La Trobe University. A fundamental area of interest is investigating the problems associated with miniaturization of the control and health monitoring sensors for such systems. While many technologies for UAV and SHM systems can be, and have been, adapted from those currently available in large manned aircraft; cost, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Research into MEMS has demonstrated that all the required parameters for control, and environment and health monitoring can be obtained from a mass-spring-damping system [4 -8], but in each case the MEMS sensor has been optimised for a single parameter. Previous research by the authors investigated the practicality of using this same mass-spring-damping structure, in a dynamic way, to enable real time reassignment from one parameter to another [9]. This paper extends the research into simulations of a more complete system including some aircraft dynamics along with sensor failure.…”
Section: Conceptmentioning
confidence: 95%
See 1 more Smart Citation
“…Research into MEMS has demonstrated that all the required parameters for control, and environment and health monitoring can be obtained from a mass-spring-damping system [4 -8], but in each case the MEMS sensor has been optimised for a single parameter. Previous research by the authors investigated the practicality of using this same mass-spring-damping structure, in a dynamic way, to enable real time reassignment from one parameter to another [9]. This paper extends the research into simulations of a more complete system including some aircraft dynamics along with sensor failure.…”
Section: Conceptmentioning
confidence: 95%
“…For example, the sensor chip model top level is shown in Figure 5, showing the nine elements and the data amalgamation for each measurement parameter. The model for each element is not shown but is based on previous work that models the element in greater detail [9].…”
Section: Conceptmentioning
confidence: 99%
“…Xue Liang et al [4] studied the correlation of a MEMS array and demonstrated its influence on the angular velocity accuracy signal. Previous studies [5,6] presented a design method and a fusion estimation method using MEMS arrays under different scenarios. Moschas Fanis et al [7] proposed a simple and effective method for testing the performance of state-of-the-art MEMS arrays in various engineering applications.…”
Section: Introductionmentioning
confidence: 99%